ANALISIS PENGARUH ANTARA LABA AKUNTANSI, LABA TUNAI, DAN ARUS KAS OPERASI TERHADAP DEVIDEN KAS PADA PERUSAHAAN WHOLESALE AND RETAIL TRADE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ryezky Ramayandez Azfash; Kamaliah '; Yesi Mutia Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study to determine the influence of accounting profit, cash profit, and cas flow operation on the cash dividend wholesale and retail trade companies in Indonesia Stock Exchange. In data collections, the author collected secondary data in which companies’ financial statement from 2007-2012 periods. The methods that used to chose the sample were purposive sampling. There are 7 companies that used as a sample in accordance with the criteria of purposive sampling. In the analysis, accounting profit, cash profit, and cash flow operation as variable independent and cash dividend as variable dependent. The results of the analyisis showed accounting profit give influence in the companies’ decision making to distribute cash dividend on the next period compared cash profit and cash flow operation. Keywords: Accounting profit, cash profit, cas flow operation, cash dividend.